Beware: The Corona Mortis, “Crown of Death” - Stephanie I. Paz; Jeffrey Y. Wang; Shan-e-Ali Haider; Richard A. Silva; Dustin Y. Yoon (Annals of Vascular Surgery - Brief Reports and Innovations, 2022)
The Corona Mortis vessel is an anastomosis between the obturator and external iliac or inferior epigastric vasculature. It can be arterial, venous, or both. Its injury is a source of severe hemorrhage during hernia repairs, urological, gynecological, and orthopedic procedures. We present a case of a 53-year-old female patient with a history of peripheral arterial disease that underwent angioplasty for limb salvage that resulted in injury of the Corona Mortis variant and a subsequent persistent pelvic hemorrhage. Hemostasis of extravasation was achieved through coil embolization and patient recovered without any complications. This is the first publication in vascular surgery literature that we are aware of where an injury can result in life-threatening hemorrhage from the Corona Mortis.